(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The grail of the study was to design, develop and characterize sustained release mucoadhesive microspheres of acyclovir and to optimize the drug release profile using response surface methodology by applying Box–Behnken design (BBD) which was equipped with three levels and three factors. Microspheres were prepared from Methocel K15M and Ethocel Standard 45 Premium using the emulsification solvent evaporation technique. The independent factors were the amounts of Methocel K15M (X1), amount of Ethocel Standard 45 Premium (X2), and RPM (X3). The dependent variables were cumulative percentage drug release (CDR) at 8 hour (Y1), bond strength (Y2), and swelling at 4 hour (Y3). To understand the effects of different factor level combinations on the responses, various response surface graphs and contour plots were prepared. Predicted values and experimental values for optimized formulation (X1 = 600 mg, X2 = 500 mg, and X3 = 336.57) was found to be in close agreement. Dhaka Univ. J. Pharm. Sci. 18(1): 1-2, 2019 (June)